Cutaneous leishmaniasis: epidemiology, treatment access and translational challenges of topical therapies - Carrer, Dolores C.; Papera, Francesca; Ríos, Diego N. (Frontiers in Microbiology, 2026)
Leishmaniasis is an orphan, vector-borne parasitic disease endemic in more than 90 countries. It displays different clinical manifestations, being the cutaneous form (CL) the most common. This presents as skin ulcers that produce significant psychosocial distress, lifelong scarring and stigmatization. Historically endemic in low-income regions in the tropics, epidemiological data and computational models forecast the continued expansion into regions further away from the Equator, both northwards and southwards. Treatments for CL are unsatisfactory and are currently the major unmet medical need for the leishmaniases. An inherent difficulty with using the available systemic drugs is that they are highly toxic and painful to administer and require second-level hospital infrastructure to manage side effects. In this context, local treatments, and in particular topical treatments for CL are particularly interesting due to their potential to be efficacious and less toxic, painful and inconvenient than systemic treatments. They could improve patient compliance and allow self-treatment, diminishing associated financial costs both for the patients and for the states that usually provide the treatments. In this work we discuss epidemiology of the disease and availability of treatments and then center on topical treatments, covering advances in preclinical and clinical studies.